2022
DOI: 10.1177/10760296211067260
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Fibrinogen to Albumin Ratio and Early Outcomes in Patients with Acute Pontine Infarction

Abstract: Background and purpose Previous studies have indicated that fibrinogen and low serum albumin levels are associated with poor outcomes of acute ischemic stroke. The role of the fibrinogen-to-albumin ratio (FAR) as a novel inflammatory and thrombotic biomarker in acute ischemic stroke is unclear. This study aims to investigate the relationship between the FAR and 3-month outcomes of acute pontine infarction. Methods: Patients with acute pontine infarction were consecutively included. All patients were followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In addition, albumin neutralizes fibrinogen binding to endothelial cells, thus antagonizing several prothrombotic effects of fibrinogen [ 108 ]. Additionally, endothelial dysfunction and blood viscosity are increased in patients with hypoalbuminemia [ 109 ]. During inflammatory states, the coagulation cascade favors thrombus formation due to the decreased synthesis and increased catabolism of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, albumin neutralizes fibrinogen binding to endothelial cells, thus antagonizing several prothrombotic effects of fibrinogen [ 108 ]. Additionally, endothelial dysfunction and blood viscosity are increased in patients with hypoalbuminemia [ 109 ]. During inflammatory states, the coagulation cascade favors thrombus formation due to the decreased synthesis and increased catabolism of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is an inflammation-related protein that participates in thrombokinesis, platelet aggregation, blood viscosity, thrombus formation, and fibrin formation ( Kim and Lee, 2014 ; Zhai et al, 2022 ). Fibrinogen is secreted in the liver and plays a role in cardiovascular risk through the regulation of coagulation and inflammation pathways ( Hou et al, 2021 ).…”
Section: Hemostasis Biomarkersmentioning
confidence: 99%
“…For example, it has been reported that a high FAR predicts poor functional outcome in patients with acute pontine infarction. 36 Previous studies also found that a high FAR might be an independent predictor of disability and death after lacunar stroke. 5 This present study showed that FAR level was significantly associated with stroke recurrence, poor functional outcome, and dependence in our LAA stroke cohort after adjusting for all confounding risk factors.…”
Section: Discussionmentioning
confidence: 94%